Estratégias para redução de sacarose em bebida láctea sabor chocolate - Louzada, Camila Affonso (2024)
Consolidated research on diseases associated with the consumption of sugary beverages has driven the use of sweeteners in their formulations. Thus, in article 1, the aim was to determine the ideal sweetness and sweetness equivalence of sucralose and potassium acesulfame in relation to sucrose in chocolate-flavored dairy beverage. Through the ideal sweetness scale and magnitude estimation, it was determined that the ideal sweetness of the beverage is 8% sucrose. Sucralose is approximately ten times sweeter than potassium acesulfame and 533 times sweeter than sucrose at the same concentration of 8%. The Hedonic Threshold Methodology (HTM) can be used to estimate how much an ingredient can be reduced or added to foods without compromising acceptance and without resulting in sensory rejection by the consumer, assisting in the determination of formulations and reducing production costs. Thus, the objective was to apply HTM to reduce the sucrose concentration in chocolate-flavored dairy beverage without compromising sensory acceptance or causing sensory rejection, varying one stimulus: sucrose; two stimuli: sucrose and sucralose; and three stimuli: sucrose, sucralose, and potassium acesulfame. In article 2, varying only the sucrose stimulus, consumers did not accept large reductions in sucrose. Health concern did not affect the values of hedonic thresholds for flavor, consistency, and overall impression. Segmentation related to loss/alteration of smell and/or taste did not influence hedonic thresholds. In article 3, a blind trial and an informed trial were conducted: in the informed trial about sucrose and sucralose, larger reductions in sucrose were allowed than in the blind trial, except for flavor. It is noted that by adding sucralose to chocolate-flavored dairy beverage, it is possible to substantially reduce the sucrose content without compromising the sensory acceptance of the product in all attributes. In article 4, the reduction of sucrose by using sucralose and potassium acesulfame led to a change in the sensory acceptance of chocolate-flavored dairy beverage regarding overall impression, and then affected color, flavor, consistency, and finally aroma. Temporal dominance of sensations data complemented HTM data, highlighting the importance of both methodologies working together to improve data analysis and applicability. Moreover, high concentrations of potassium acesulfame may alter the product, and at lower concentrations, they may help reduce the sucrose content and please the consumer. Although partial substitution of sucrose by a mixture of sucralose and potassium acesulfame allows reductions in sucrose concentration, partial substitution by sucralose alone allows greater reductions. It is concluded that adding sucralose to dairy beverage allows greater reductions in sucrose than simply reducing sucrose without adding sweetener, as well as greater reductions than the mixture of sucralose and potassium acesulfame. Finally, for the first time, hedonic thresholds were determined with the substitution of sucrose by sweeteners.